Edwin G. Pulleyblank. Lexicon of Reconstructed Pronunciation in Early Middle Chinese, Late Middle Chinese and Early Mandarin. Vancouver: UCB Press, 1991. VII+ 488 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1993)
-